PENGARUH PELAYANAN JASA TERHADAP KEPUTUSAN PEMBELIAN TIKET PESAWAT PADA PT. DAYAKINDO KALIMANTAN TIMUR UTAMA TOUR TRAVEL - Herawati, Novilinda (EKONOMIA, 2013)
Novenlinda Herath, EFFECT OF SERVICE DECISIONS TO PURCHASE TICKETS IN. DAYAKINDO KALIMANTAN EAST MAIN TOUR TRAVEL increasingly sharp competition services sector may cause a decrease in the sales turnover resulted in the survival of the company, management is required to think aspects of services includes Countability, Responsiveness, Assurance, attention and physical facilities. Responder analysis results concluded the purchase decision variable air tickets of all services provided by PT. Dayakindo East Kalimantan Main Tour Travel the average score is above 3.9733 score an average of 3, can be interpreted is quite satisfactory with a standard deviation of 0.56013 average. Concurrent analysis of service indicators: variables Countability, Responsiveness, Assurance, attention and physical facilities with relationship and 24.5% 75.5% specified indicators. indicators of service that has been studied gave a strong belief that the variable PT services. Dayakindo Main Tour Travel East Kalimantan can be used to predict or match the purchase decision variable air tickets. In general, the results of the study be quite good but there are things that need to be evaluated especially regarding other factors that influence the decision of airline ticket purchase, to the management of PT. Dayakindo East Kalimantan Main Tour Travel should be responsive to the development of competition in a similar business, so that PT. Dayakindo Main Tour Travel East Kalimantan still exist in the trade.Â